When trust is lost: the impact of interpersonal trauma on social interactions. Issue 6 (25th July 2018) - Bell, Victoria; Robinson, Benjamin; Katona, Cornelius; Fett, Anne-Kathrin; Shergill, Sukhi
Abstract: Background: Trauma due to deliberate harm by others is known to increase the likelihood of developing Post-Traumatic Stress Disorder (PTSD). This is the first study investigating basic and dynamic trust in 'interpersonal' PTSD. Methods: Thirty-two participants with PTSD and 22 healthy controls played a novel multi-round version of a monetary investment protocol, the so-called 'Trust Game', a task from the behavioural economics literature, which is considered to involve trust and reciprocity. We used two 'Trust Games' including cooperative and unfair partners. Results: Findings showed an effect for lower basic investment in PTSD compared to healthy controls, that trended towards significance ( p = 0.09). All participants showed behavioural flexibility and modified their trust based on behavioural cues from their cooperative and unfair game partners. However, participants with PTSD made significantly lower investments towards the cooperative partner than controls. Investments towards the unfair partner did not differ between groups. Higher trauma scores were associated with lower levels of trust-related investments towards the cooperative but not the unfair game partner. Conclusion: The association between reduced trust towards cooperative others in individuals who experienced interpersonal trauma could indicate acquired insensitivity to social rewards or inflexible negative beliefs about others as a sequel of the traumatic experience, which increases in a dose response relationship with the severity of the trauma. A specific focus on cooperation and trusting behaviour could provide a treatment target for future cognitive and pharmacological interventions.